2022
DOI: 10.1001/jamaophthalmol.2021.6067
|View full text |Cite
|
Sign up to set email alerts
|

Association of Pegcetacoplan With Progression of Incomplete Retinal Pigment Epithelium and Outer Retinal Atrophy in Age-Related Macular Degeneration

Abstract: IMPORTANCE Change in areas of incomplete retinal pigment epithelium (RPE) and outer retinal atrophy (iRORA) within eyes with geographic atrophy (GA) might reflect similar changes among eyes with drusen but no GA.OBJECTIVE To evaluate the potential association of pegcetacoplan with progression of iRORA in eyes with GA secondary to AMD. DESIGN, SETTING, AND PARTICIPANTSThis post hoc analysis of the phase 2 multicenter, randomized, single-masked, sham-controlled FILLY trial of intravitreal pegcetacoplan for 12 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…47,48 Besides incident iRORA (or nGA) as an endpoint, the rate of iRORA to RPE-atrophy transition distant to the junctional zone has been proposed as an endpoint. 49 In another post-hoc study of the FILLY trial, a reduced iRORA to RPE-atrophy transition rate in eyes treated with pegcetacoplan was reported. 50 Further studies are warranted to examine whether the observed lesser thinning at the level of the ONL along contour-lines reflects the sum of decreased focal thinning primarily, 50 or reduced thinning in a 'macula-wide' manner.…”
Section: Discussionmentioning
confidence: 95%
“…47,48 Besides incident iRORA (or nGA) as an endpoint, the rate of iRORA to RPE-atrophy transition distant to the junctional zone has been proposed as an endpoint. 49 In another post-hoc study of the FILLY trial, a reduced iRORA to RPE-atrophy transition rate in eyes treated with pegcetacoplan was reported. 50 Further studies are warranted to examine whether the observed lesser thinning at the level of the ONL along contour-lines reflects the sum of decreased focal thinning primarily, 50 or reduced thinning in a 'macula-wide' manner.…”
Section: Discussionmentioning
confidence: 95%
“…This concept was more recently incorporated by the Classification of Atrophy Meeting (CAM) consortium as a part of incomplete RPE and outer retinal atrophy (iRORA) 57 , 58 . Besides incident iRORA (or nGA) as an endpoint, the rate of iRORA to RPE-atrophy transition distant to the junctional zone has been proposed as an endpoint 59 . In another post-hoc study of the FILLY trial, a reduced iRORA to RPE-atrophy transition rate in eyes treated with pegcetacoplan was reported 60 .…”
Section: Discussionmentioning
confidence: 99%
“…Besides incident iRORA (or nGA) as an endpoint, the rate of iRORA to RPE-atrophy transition distant to the junctional zone has been proposed as an endpoint 59 . In another post-hoc study of the FILLY trial, a reduced iRORA to RPE-atrophy transition rate in eyes treated with pegcetacoplan was reported 60 . Further studies are warranted to examine whether the observed reduced thinning at the level of the ONL along contour-lines reflects the sum of decreased focal thinning primarily 60 , or reduced thinning in a ‘macula-wide’ manner.…”
Section: Discussionmentioning
confidence: 99%
“…Post hoc analysis suggested pegcetacoplan may be useful in AMD prior to the development of GA [ 66 ]. Incomplete RPE and outer retinal atrophy (iRORA) without neovascularization are considered precursor lesions to GA, while progression to complete RPE and outer retinal atrophy (cRORA) without neovascularization are synonymous with GA.…”
Section: Current Therapeutic Targetsmentioning
confidence: 99%
“…In the trial, patient eyes receiving pegcetacoplan possessed lower rates of progression from iRORA to cRORA. As such, although findings did not achieve statistical significance, pegcetacoplan may prevent the incidence of GA [ 66 ]. However, in the FILLY study, new-onset wet AMD was more prevalent in the pegcetacoplan groups compared with the sham arm.…”
Section: Current Therapeutic Targetsmentioning
confidence: 99%